Assessing the benefits of education in early childhood: Evidence from a Pre‐K lottery in Georgia. - Woodyard, Henry; Sass, Tim; Fazlul, Ishtiaque (Economic Inquiry, 2025)
Using enrollment lotteries for over‐subscribed school‐based sites in Georgia's universal pre‐K program, we analyze the impact of participation on elementary school outcomes. We find that lottery‐winning school‐based Georgia Pre‐K enrollees enter kindergarten more prepared in both math and reading than non‐winning peers. Gains fade by the end of kindergarten, and some negative achievement effects emerge by grade 4. Free‐and‐reduced‐price meal (FRPM) students benefit more compared to non‐FRPM students in later grades, suggesting greater benefits from attendance for disadvantaged students. Although we found no effects on discipline, school‐based pre‐K enrollees had one fewer absence each grade after kindergarten.